PENERAPAN NATURAL LANGUAGE PROCESSING ALGORITME SBERT PADA APLIKASI CHATBOT PENERIMAAN MAHASISWA BARU UNIVERSITAS PAMULANG - Aji Sakti Ardiansyah; Kahfi Heryandi Suradiradja (Informatika: Jurnal Teknik Informatika dan Multimedia, 2026)
The New Student Admission (PMB) process at Pamulang University currently relies on one-way information channels such as Instagram and brochures only at designated posts. This condition limits access to information for prospective students, especially when they require quick and detailed answers regarding registration requirements, schedules, and tuition fees. Furthermore, the large number of applicants in each admission period makes manual inquiry services inefficient and prone to delays. Therefore, a technology-based solution must provide interactive, fast, and accurate information services. This study aims to develop a Chatbot based on Natural Language Processing (NLP) using the Sentence-BERT (SBERT) algorithm to support the PMB process at the Informatics Engineering Program at Pamulang University. The Chatbot is designed to provide accurate and relevant automated responses to prospective students' inquiries regarding PMB. The SBERT algorithm enhances the Chatbot’s ability to understand sentence meanings and deliver contextual responses. The software development adopts the Waterfall model, encompassing requirements analysis, system design, implementation, and testing phases. The expected outcome is a Chatbot system with- high response accuracy that improves efficiency and accessibility of PMB information services. This research is expected to contribute to the implementation of NLP technology in academic environments.